Making the city of commons: popular economies between urban conflicts and capitalistic accumulation - Castronovo, Alioscia (Tracce urbane. Rivista italiana transdisciplinare di studi urbani, 2018)
Over the last decades urban popular economies emerged in metropolitan spaces in Latin America as an assemblage of productive and reproductive activities, subjectivities, practices, spaces, infrastructure and social relationships. By analyzing as part of an ethnographic fieldwork two experiences of self managed labour cooperative experiences in Buenos Aires, this paper aims to reflect on the processes of building up popular infrastructures as new possible institutions and configurations of common urban life, analyzing potentialities and ambivalences that emerges from the ambiguous relationships that popular economies and self managed factories establish with the market, the State and finance. Negli ultimi decenni le economie popolari sono emerse nelle aree metropolitane in America Latina come un assemblaggio di attività produttive e riproduttive, spazi, pratiche, infrastrutture e relazioni sociali. Analizzando a partire da un lavoro di ricerca etnografica due esperienze di autogestione cooperative del lavoro a Buenos Aires, questo contributo si pone l’obiettivo di riflettere sui processi di costruzione di infrastrutture popolari, nuove possibili istituzioni e configurazioni di vita urbana in comune, analizzando potenzialità e ambivalenze che emergono dale relazioni ambigue che economie popolari e fabbriche recuperate stabiliscono con il mercato, lo Stato e la finanza.